Analisis Perbandingan Kontrak Tradisional dan Kontrak Berbasis Kinerja (KBK) Berdasarkan Risiko Persepsi Kontraktor dengan Metode Analytical Hierarchy Process (AHP) - Fauziyah, Shifa; Wibowo, M. Agung; Suliantoro, Hery (Department of Civil Engineering, Diponegoro University, 2016)
Two types of contracts that are used in the road project is a traditional contract (Unit Price) and performance based contract (Lump Sum). Both types of contracts have their own risks. Therefore, it is necessary to measure which type of contracts is more risky between traditional contract and performance-based contract from the perspective of the contractor using Analytical Hierarchy Process. Analytical Hierarchy Process (AHP) is a method used to find a weight where the intensity of the risks using traditional contract and performance-based contract can be measured and analyzed. This research took sample for project with a traditional contract is Kendal – Semarang Road Project. While the samples for the project with a performance based contract is Semarang – Bawen Road Project. The results of the calculation by the alternative assessment, are the higher rank is performance based contract which is 0.56 (56%), while traditional contract is the second with the total score 0.44 (44%). The mean is performance based contract more risky than traditional contract from the perspective of the contractor.